Requirements Analysis and Initial Use Case Design of a Web-Based Student Data Management Information System at SMP Negeri 37 Bandung - Annisa Nur Rohmah; Muhammad Khali Fauzy; Micky Ardian Ananta; Darmawan Yudhanegara (Applied Engineering: Jurnal Rekayasa dan Sains Terapan, 2026)
Student data management is an essential component of school administration because it supports identity recording, administrative reporting, and information retrieval for institutional decision-making. However, in many schools, student data are still managed manually or using simple spreadsheet-based applications, which may cause data duplication, input errors, slow data retrieval, and inefficiency in report preparation. This study aims to analyze the requirements and develop an initial use case design for a web-based student data management information system at SMP Negeri 37 Bandung. The study employed a descriptive qualitative approach focusing on the early stage of the information system development cycle, namely requirement analysis. Data were collected through observation, interviews with school administrative staff, and literature study. The collected data were analyzed descriptively to identify the current condition of student data management, functional requirements, non-functional requirements, user roles, and initial data structure. The results show that the proposed system should provide several main functions, including adding student data, editing student data, deleting student data, displaying student data, searching student data, and printing student data reports. The system also needs to fulfill non-functional requirements related to accessibility, security, usability, and reliability. The proposed use case design identifies administrative staff as the main actor responsible for managing student data through the system. This study contributes an initial requirement analysis and use case design that can serve as a foundation for further system design, database development, interface design, implementation, and testing.